The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.24238/13221-13-1-203
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis-osteogenesis coupling: a key element in bone physiology and regeneration

Abstract: Bone represents a well vascularized structure which is remodelled and renewed continuously. It consists of osteoblasts, osteoclasts and osteocytes which have a precise role in the context of endochondral and intramembranous ossification. While the link between the bone tissue, bone marrow and the haematopoiesis is crucial for the generation of progenitor bone forming cells, recent research indicates that bone physiology as well as bone healing, repair and regeneration is directly dependent on bone angiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Large numbers of studies have highlighted the vital roles of coupled angiogenesis and osteogenesis during bone healing process, particular for the cross-talk between endothelial cells and osteogenic cells [ 30 , 31 ]. Recently, papers also demonstrated that, apart from proosteogenesis, CGRP also displayed a potential promotive role in angiogenesis and vasodilatory of injury bone site, which in turn indirectly promote osteogenesis [ 13 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Large numbers of studies have highlighted the vital roles of coupled angiogenesis and osteogenesis during bone healing process, particular for the cross-talk between endothelial cells and osteogenic cells [ 30 , 31 ]. Recently, papers also demonstrated that, apart from proosteogenesis, CGRP also displayed a potential promotive role in angiogenesis and vasodilatory of injury bone site, which in turn indirectly promote osteogenesis [ 13 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…( DiPietro, 2016 ; Shi et al, 2023 ). During bone development and regeneration, the growth of blood vessels are coupled with osteogenesis ( Boston et al, 2021 ; Schott et al, 2021 ). Blood vessels are important for the transport of nutrients, oxygen, ions, circulating cells and facilitate the removal of metabolic waste ( Rademakers et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%